Electrochemical characteristic of ErBa2Cu3O7-8 superconductor synthesized via co-precipitation and solid-state reaction - Nazarudin, Muhammad Farhan (2011)
High temperature superconductors (HTSC) of microcrystalline ceramic material ErBa2Cu3O7-δ (ErBCO) have been successfully synthesized via co-precipitation (COP) using metal acetate precursors, and conventional solid state method (SS). Comparisons were made on the superconducting properties and electrochemical behavior of ErBCO from both methods. Resistivity versus temperature measurements (R-T) showed that all samples exhibited very good metallic behavior. For the COP samples, the sintering temperature was varied from 920-950 °C with the best zero critical current, TC(R=0) = 91.4 K obtained for the sample sintered at 920oC. The TC(R=0) = 90.9 K was obtained for the SS sample sintered at the same temperature. X-ray diffraction (XRD) data showed single phase samples of an orthorhombic structure. The formation of non superconducting phases (impurities) was observed when the COP samples were sintered above 920oC. Scanning electron micrographs (SEM) showed grains of size ≤ 40 nm were randomly distributed for all highly compacted samples. However, sample prepared via COP exhibited smaller pores as compared with SS sample. The electrochemical behaviour of the samples had been studied by the cyclic voltammetry (CV), chronoamperometry (CA) and chronocoulometry (CC) techniques. The samples were mechanically attached to glassy carbon (GC) electrode and immersed in NH4Cl electrolyte solution. NH4Cl electrolyte was chosen because it has a ligand bearing group with strong complexing ability with copper ion. Multiple cycling tests were carried out to observe the reproducibility and stability of the superconducting surface against the electrolyte. Four characteristics peaks were detected in cyclic voltammogram of ErBCO. There were two sets of peaks observed which could be attributed to the Cu2+/Cu1+ and Cu1+/Cu0 redox couples. This showed that the copper planes in the superconductor played a major role in the surface electrochemical processes. The cyclic voltammetric behavior exhibited from both samples was found to be affected by concentration, temperature and pH of the electrolyte. From CA and CC studies, diffusion coefficient, D was 3.4516 x 10-3cm2/s for COP and 2.3677 x 10-4cm2/s for SS respectively while the amount of charge, Q adsorbed on the electrode surface was 5.4413 μC/ cm2 for COP and 4.7383 μC/ cm2 for SS, respectively.